Disparities in the impact of drought on agriculture across countries - Hayden Freedman; Amir AghaKouchak; Angela J. Rigden; André van der Hoek; Bill Tomlinson (Scientific Reports)
Abstract Over the last several decades, droughts driven by climate change have damaged agricultural production as the planet warms. It is crucial for the future of the global food supply to develop effective adaptation strategies. However, not all countries and regions are affected equally by drought. We fit a hierarchical Bayesian model with a dataset containing 60 years of country-level drought and agricultural productivity data to probabilistically identify the susceptibility of various countries and regions to drought. We find that regions such as Eastern Africa and Southern Asia are highly susceptible to drought, with each region exhibiting a >90% chance that drought has negatively affected agriculture, leading to estimated historical agricultural losses of >14%, while Eastern Asia is the most drought-resilient region, with only a 44% probability that drought has negatively affected agriculture in this region. The results of this study can help inform the allocation of future resources to enhance agricultural resilience in the most vulnerable regions. Additionally, they provide a foundation for case studies examining specific countries or regions that demonstrate notable resilience or susceptibility to drought.